TRADISI MAKAN BAJAMBAU DI DESA SALO TIMUR KECAMATAN SALO KABUPATEN KAMPAR - Hafizh, Abdul; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Makan bajambau is eating together in one serving which has been generation to generationfrom previous ancesturs. Makan bajambau is a original tradition from Kampar regency.Makan bajambau tradition is usually by Kampar people especially in Salo Timur village onwedding ceremony, aqiqah, 7 day of ecease, another big days of Islam religion, andinauguration of Ninik Mamak and local functionary. Before start makan bajambau NinikMamak of ritual chief will open it with ritual present are doing by simondo people with NinikMamak who has come. In makan bajambau people usually use salver serving, strory saver andthree foot tray, while the food which sarve in this makan bajambau usually are meat, vegetable,fish, fresh vegetable and dadio dessert. Nowaday people more make variation the good on thatsarve. In this research, the researchers do researching abaout how to implemention of makanbajambau tradition. In this research, the researchers use functionalism theory and socialysystem theory, with many of respondent are many and people which are local functionary,Ninik Mamak, society figure, religious agure, and local government officials. The results ofthis study indicate that the implementation of the tradition makan bajambau still exist and stilldone by Kampar district community especially village Salo Timur, while the values in makanbajambau is the social value of society prioritizing togetherness and mutual mutilation and thevalue of adat gives priority the present generation in order to keep preserving and preservingthis tradition so as not to disappear in today’s modern era.Keywords: Tradition, Makan Bajambau, Value